Protection of Well-Known Trademarks Against Bad Faith: The Starbucks Dispute - Azwa Khaliza; Naila Syafa AzZahra; Restu Ramania; Ikhwan Aulia Fatahillah (Journal of Human Interaction and Social Studies, 2026)
The increasing globalization of trade has intensified trademark disputes involving well-known trademarks, particularly those arising from registrations made in bad faith. In contemporary trademark law, protection is no longer confined to similar goods or services, as the unauthorized use of well-known marks on dissimilar goods may create consumer confusion, dilute trademark reputation, and result in unfair competition. This study aims to examine the legal criteria for determining well-known trademark status and to analyze the legal construction of bad faith in trademark registration involving dissimilar goods through the Starbucks trademark dispute in Indonesia. The research employs a normative legal research method using statutory, conceptual, and case approaches. Primary, secondary, and tertiary legal materials were collected through library research and analyzed using qualitative descriptive methods. The findings reveal that the status of a well-known trademark is determined not only by formal registration but also by public recognition, promotional intensity, international reputation, duration of use, and market penetration. The study further demonstrates that trademark registration for dissimilar goods may constitute bad faith when intended to exploit the goodwill of a famous mark. Supreme Court Decision No. 836 K/Pdt.Sus-HKI/2022 confirms that the first-to-file principle cannot be applied rigidly when evidence of bad faith and the protection of a well-known trademark are at stake. The decision reflects a substantive approach that prioritizes fairness, consumer protection, and the prevention of unfair competition. These findings highlight the importance of balancing procedural certainty with substantive justice in strengthening the protection of well-known trademarks within Indonesia’s trademark law framework.